Comorbidity of Anxiety and Hypertension: Common Risk Factors and Potential Mechanisms - Tingting Qiu; Zhiming Jiang; Xuancai Chen; Yehua Dai; Hong Zhao (International Journal of Hypertension)
Anxiety is more common in patients with hypertension, and these two conditions frequently coexist. Recently, more emphasis has been placed on determining etiology in patients with comorbid hypertension and anxiety. This review focuses on the common risk factors and potential mechanisms of comorbid hypertension and anxiety. Firstly, we analyze the common risk factors of comorbid hypertension and anxiety including age, smoking, alcohol abuse, obesity, lead, and traffic noise. The specific mechanisms underlying hypertension and anxiety were subsequently discussed, including interleukin (IL)-6 (IL-6), IL-17, reactive oxygen species (ROS), and gut dysbiosis. Increased IL-6, IL-17, and ROS accelerate the development of hypertension and anxiety. Gut dysbiosis leads to hypertension and anxiety by reducing short-chain fatty acids, vitamin D, and 5-hydroxytryptamine (5-HT), and increasing trimethylamine N-oxide (TAMO) and MYC. These shared risk factors and potential mechanisms may provide an effective strategy for treating and preventing hypertension and comorbid anxiety.